THE ABILITY OF STUDENTS OF ENGLISH STUDY PROGRAM 2017/2018 YEAR, ISLAMIC UNIVERSITY OF INDRAGIRI TO DISTINGUISH PRESENT PARTICIPLE FROM GERUND - Agus Mustajib (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2018)
Language is purely human and non-instinctive method because language is the most frequently used and most highly developed form of human communication. And language is a distinctly human instrument, although other animals produce sounds and noises, the human language alone is articulated into words and alone is capable of expressing an infinite variety of thought. Languages are not just sets of symbols. They also often conform to a rough grammar, or system of rules, used to manipulate the symbols. The grammar of a language is a complex and highly structured affair because it operates in terms of concepts and categories which have to be defined in the same way. So we need grammar in using English and the understanding about grammar also influences our ability in English. The students of English study program 2017/2018 year, Islamic university of Indragiri are the students who are obliged to use English in almost all subjects. So, the researcher is eager to know their ability to distinguish present participle from gerund can be as a measure and correction for them how far their understanding about English. In conclusion, the students of English study program to distinguish present participle and gerund has percentage, there was 62.02 % the correct answer, while the percentages of the incorrect answer was 37.98 %. From the percentage of the correct answer above can be said that the ability of the 2017/2018 year students of English study program, Islamic University of Indragiri in distinguishing present participle from gerund is good.